Kepuasan Masyarakat terhadap Pelayanan Penjualan Tiket Pada PT. Pelayaran Nasional (PT. Pelni) Tanjungpinang - SRI AMBAR RINAH; SY. Rafenska Natania; DESRIAN EFFENDI (STISIPOL Raja Haji, 2021)
Sea transportation is a means that cannot be separated from Indonesia, this is because the territory of Indonesia consists of most of the islands and waters. PT. Pelni is a state-owned company that provides various services related to shipping, such as ticket sales, shipping agents, ship loading and unloading, warehousing, ship charters and so on. Based on data from PT PELNI, it is known that ticket sales have decreased since the last few years starting from 2015 to 2020. There are still prospective passengers who complain about the services provided by PT. Pelni Tanjungpinang, where the administrative process for buying tickets is still convoluted. Then the flow of services provided is not in an orderly manner, this is evidenced when people queue at the time of purchasing tickets. Furthermore, prospective passengers feel that the officer's concern in providing services to prospective passengers is still lacking. For this reason, the community satisfaction survey is a benchmark to determine community satisfaction. The purpose of this study was to determine the satisfaction of prospective passengers with ticket sales services by PT. national shipping (PT. Pelni) Tanjungpinang. This type of research is descriptive with a quantitative approach. the population in this study were all people who had visited PT. PELNI Tanjungpinang City amounted to 5,226 people/month. The sample in this study used the Slovin formula with a total sample of 98 respondents. The sampling technique used is the accidental sampling technique. The data collection techniques are questionnaire, observation, and documentation. While the data used are primary and secondary data. The data analysis technique is quantitative data analysis technique. The results of this study are based on the index value for services at PT. Pelni Tanjungpinang is 2,98340. This value is converted to a base value of 25, so the result of the IKM value is 74.58. Based on these calculations, it can be said that the service quality at PT Pelni Tanjungpinang is C, and it means that the service at PT Pelni Tanjungpinang is not good. So it can be concluded that the overall satisfaction of prospective passengers from all indicators is less satisfied, indicated by the percentage of 65.3%. Suggestions that can be given are PT. Pelni improves the existing service flow by providing a queue number so that the service mechanism becomes more regular.